An advanced technique of laser distance meter calibration - Chinchusak, Wanchai; Phimsri, Chanin; Homchoey, Pisit; Nonthasirit, Sarinya (Bulletin of Applied Sciences, 2022)
Recently, the laser distance meter mostly employed in construction area, and other related to measurement applications. Whereas, the length calibration laboratory certainly needs to find out both technical calibration and their traceability. This research presents the advanced technique of smart measuring probe for performance test method of laser distance meter, based on ISO 16331-1 (2012). The minimized measurement uncertainties are 0.64 mm, 0.73 mm, and 0.80 mm of 3 samples, at maximum range of reference distance 20 m, the confident level at approximately 95%.